Press representations of the national healing process in Zimbabwe post 2008 presidential election - Mapuwei, Nyasha (International Journal of Social Sciences and Entrepreneurship, 2019)
The journey to the realization of unity in Zimbabwe following the bruising and disputed 2008 presidential election has been marked by many challenges that include political, social, cultural, commercial, religious and historical. But the Zimbabwean dream for unity is very much alive. This dream saw the creation of a national healing committee to spearhead efforts towards unity after the creation of the government of national unity in 2009. This move brought hope for integration of people from different political party backgrounds in a calm and promising Zimbabwe. However, the past four years of the existence of the government of national unity has revealed a consistent paling of the unity hope as press representations and discourses reflect events of a shattered unity dream. This paper seeks to explain how, why and to what extent press representations on the national healing process in three national daily newspapers, The Herald, Daily news and News Day, affected its implementation. The main research method used in this study is content analysis. Based on the theories of gate-keeping, agenda setting, representation, and referring to media and political economy theories, this paper argues that press representations in Zimbabwe had a direct impact on the success and/or failure of the initiative. The analysis suggests that the overall underlying tone of newspaper articles on the national healing process were dismissive, negative and contributed very little towards fostering unity and tolerance in the Zimbabwean political life.